Assessing the recyclability of spent fluid catalytic cracking catalyst for sustainable dry reforming of methane - Ahmed Abotaleb (9596108) (2024)
Spent catalysts are a significant source of metal-containing waste, and their disposal can pose environmental and economic challenges. Recycling these spent catalysts can not only reduce waste but also recover valuable metals, which can be used as raw materials for synthesizing new catalysts, as well as produce substrates for other industrial catalytic applications. Here we explore the recycling of spent fluid catalytic cracking catalysts (FCCCs) to obtain zeolite-based materials. Such substrates have been further doped with nickel via wet impregnation method to generate fresh catalysts for dry reforming of methane (DRM) reaction. Comprehensive analyses, including X-ray diffraction (XRD), BET surface area, scanning and transmission electron microscopy (SEM and TEM), H2-temperature programmed reduction (H2-TPR), NH3-temperature programmed desorption (NH3-TPD), and Ni dispersion via H2-pulse chemisorption, were employed to characterize these catalysts. The performance of these recycled zeolite materials was evaluated and benchmarked against commercial zeolites. Our findings reveal that acid-leached, recycled zeolite obtained from spent FCCC catalyst results in the highest overall CO2 and CH4 conversion among the studied catalysts, as well as exhibiting a high stability over 20-hour testing, underscoring the potential of recycling strategies in catalyst production. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2024.132356